1982
DOI: 10.1130/mem156-p57
|View full text |Cite
|
Sign up to set email alerts
|

6: Keweenawan intrusive igneous rocks

Abstract: A bstractThe Keweenawan intrusive rocks of the Lake Superior region may be conveniently divided into alkaline intrusions, layered tholeiitic intrusions, and quartz and olivine tholeiite dike and sill swarms. Within each group is a characteristic internal stratigraphic succession of rock types. The alkaline rocks are characterized by successions of fractionated, undersaturated to saturated gabbroic through alkalic differentiates. On the basis of data from the Duluth Complex, the layered tholeiitic intrusions ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…These observations support Mitchell and Platt's ( 1 9 8 2~) and Weiblen's (1982) suggestions that the Coldwell magmas were emplaced at a triple junction associated with a "failed arm" during the waning of the rifting episode. , however, found no compelling evidence for the existence of a triple junction in the Lake Superior region.…”
Section: Regional Tectonic-petrogenetic Settingsupporting
confidence: 86%
“…These observations support Mitchell and Platt's ( 1 9 8 2~) and Weiblen's (1982) suggestions that the Coldwell magmas were emplaced at a triple junction associated with a "failed arm" during the waning of the rifting episode. , however, found no compelling evidence for the existence of a triple junction in the Lake Superior region.…”
Section: Regional Tectonic-petrogenetic Settingsupporting
confidence: 86%
“…They argued further that their interpretation supports the association of the Coldwell intrusion to the Keweenawan rifting event with the felsic rocks being derived by differentiation of the basic parent magma. In this context Mitchell and Platt (1982) and Weiblen (1982) have suggested that the complex might represent the "failed arm" of a Keweenawan rift triple junction. In contrast Halls (1978) and…”
Section: Geology and Samplingmentioning
confidence: 96%
“…The Sonju Lake intrusion is the most completely differentiated mafic layered intrusion recognized in the Keweenawan magmatic system (Stevenson, 1974;Weiblen, 1982). The intrusion is a shallow (15-30°) south-to southeast-dipping, 1,200-m-thick sheet, which has an apparent strike length of over 15 km (based on its aeromagnetic signature, Fig.…”
Section: Southern Beaver Bay Complexmentioning
confidence: 98%